On Tensor (C) of AK Manifold (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this study, we examine the Concircular Curvature Tensor (C) of an almost kahler manifold, which indicates that W2, where W2 stands for the almost kahler manifold, presents one of the almost Hermitian manifold constructions' geometrical characteristics. These results are summarized, with emphasis on the main findings. This tensor's typical Riemannian curvature symmetry features have been proven